The Influence of Investigative Audit Procedure Accuracy and Professional Skepticism on Digital Fraud - sukma, whida Permata; Meikhati, Ety; Hanifah, Umi (International Journal of Indonesian Business Review, 2026)
This study aims to examine the effect of the appropriateness of investigative audit procedures and professional skepticism on auditors' ability to detect digital fraud. A quantitative approach was employed using primary data collected from 80 auditors working at Public Accounting Firms (KAPs) in the Surakarta and Special Region of Yogyakarta (DIY), Indonesia. The data were analyzed using multiple linear regression with SPSS version 27. The findings reveal that the appropriateness of investigative audit procedures and professional skepticism both have a positive and significant effect on auditors' ability to detect digital fraud. These results suggest that implementing investigative audit procedures tailored to digital forensic practices, together with maintaining a high level of professional skepticism, plays a crucial role in enhancing auditors' capability to identify increasingly sophisticated digital financial fraud. Therefore, Public Accounting Firm (KAP) need to improve auditor competency in implementing investigative audit procedures that are appropriate to the characteristics of digital fraud and strengthen the application of professional skepticism through continuous training and development.